Partnerships on Colorado conservation lands: social-ecological outcomes of collaborative grazing management - Monlezun, Anna Clare, author; Lynn, Stacy, advisor; Boone, Randall, committee member; Jones, Kelly, committee member; Rhoades, Ryan, committee member (Colorado State University. Libraries, 2022)
To view the abstract, please see the full text of the document.
Keywords: ecosystem science; rangeland management; sustainable agriculture; human dimensions; collaborative conservation; simulation modeling